2008
DOI: 10.1111/j.1752-4571.2008.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling genetic connectivity in sticklebacks as a guideline for river restoration

Abstract: Estimating genetic connectivity in disturbed riverine landscapes is of key importance for river restoration. However, few species of the disturbed riverine fauna may provide a detailed and basin-wide picture of the human impact on the population genetics of riverine organisms. Here we used the most abundant native fish, the three-spined stickleback (Gasterosteus aculeatus L.), to detect the geographical determinants of genetic connectivity in the eastern part of the Scheldt basin in Belgium. Anthropogenic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(143 citation statements)
references
References 63 publications
7
134
2
Order By: Relevance
“…Barson et al (2009) also studied guppy population genetics in the Marianne River and five surrounding watersheds in northern Trinidad and found that, at a coarse scale, genetic diversity was much higher in downstream populations in these highly dendritic watersheds. In contrast, these patterns were not found in the Scheldt River in Belgium, where threespine stickleback (Gasterosteus aculeatus) migration across weirs is downstream biased (Raeymaeker et al 2008). However, this watershed is significantly larger (110 times) than the Rye or Marianne, potentially allowing other ecological interactions or unsampled populations to obscure the pattern.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Barson et al (2009) also studied guppy population genetics in the Marianne River and five surrounding watersheds in northern Trinidad and found that, at a coarse scale, genetic diversity was much higher in downstream populations in these highly dendritic watersheds. In contrast, these patterns were not found in the Scheldt River in Belgium, where threespine stickleback (Gasterosteus aculeatus) migration across weirs is downstream biased (Raeymaeker et al 2008). However, this watershed is significantly larger (110 times) than the Rye or Marianne, potentially allowing other ecological interactions or unsampled populations to obscure the pattern.…”
Section: Discussionmentioning
confidence: 59%
“…In an extensive literature review conducted for this study, only 27 articles examined population genetics in dendritic systems where asymmetric movements likely occurred, and only seven studying fish (Yamamoto et al 2004;Wofford et al 2005;Crispo et al 2006;Hanfling and Weetman 2006;Deiner et al 2007;Raeymaeker et al 2008;Barson et al 2009), one studying aquatic plants (Fer and Hroudova 2008), and one studying zooplankton (Derry et al 2009) provided appropriate systems to investigate or evaluate the results from our modeling exercises. Although there are many empirical studies of the population genetics of aquatic species in fragmented environments or exhibiting asymmetric migration (Saillant et al 2004;Heggenes and Red 2006;Haponski et al 2007;Reid et al 2008;Chen et al 2009), there are few in dendritic systems that include comprehensive sampling of headwaters, intermediate branches, and the main stem, and none that allow for comparisons of local and overall genetic diversity between similar watersheds that differ only in the capacity for dispersal or dendricity.…”
Section: Discussionmentioning
confidence: 99%
“…Agriculture and forestry Broadhurst et al 2008;Friedman et al 2008;Mercer et al 2008 Anthropogenic disturbances Angilletta et al 2008;Carlson and Seamons 2008;Einum et al 2008;Haugen et al 2008;McClure et al 2008a;Waples et al 2008;Williams et al 2008;Wood et al 2008 Climate change Aitken et al 2008;Bell and Collins 2008;Crozier et al 2008;Purcell et al 2008Conservation Funk et al 2008Garroway et al 2008;Latta 2008;McClure et al 2008a;Nomura 2008;Olsen et al 2008;Raeymaekers et al 2008 Table 1). Published papers also focused on a wide diversity of organisms of applied importance, including plants, animals and microbes (Table 2).…”
Section: Topic Referencesmentioning
confidence: 99%
“…Then the exchange of genes between populations determines the relative effects of selection and genetic drift (Balloux and Lugon-Moulin, 2002). The relationships between gene flow and population genetic structure have been the subject of many studies during several decades (Slatkin,1985;Bohonak,1999;Fraser et al, 2004;Crispo et al, 2006;Raeymaekers et al, 2008;Blanchet et al, 2010). To infer individual movements between populations, and predict their consequences on population genetic structures and evolutionary potential are one of the most important issues in the management of species (Crandall et al, 2000;Fraser and Bernatchez, 2001;Frankham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%